Mahkamah Konstitusi Sebagai Sarana Check and Balances Keberadaan Undang-undang - Sari, Estika (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
This article tried to describe the existence of the Court of Constitution (Mahkamah Konstitusi) in Indonesian law system, especially in implementing its right to test the legality of law in relating to constitution. As we may have known, the amendment of Indonesian Constitution 1945 has declared the existence of this Court of Constitution and gave it the authority to test the rightness or legality of law either formally or materially. In other words, this institution function as an instrument of check and balance of the existence of Indonesian law. Kata kunci: Mahkamah Konstitusi, Undang-undang, Uji Materil, Uji Formil